Ray Donovan. Season one [videorecording (DVD)] - Schreiber, Liev; Voight, Jon, 1938-; Malcomson, Paula, 1970-; Marsan, Eddie; Mihok, Dash, 1974-; Bauer, Steven, 1956-; Moennig, Kate, 1976-; Hall, Pooch, 1976- (Paramount Pictures : CBS DVD, 2014)
Ray Donovan is the go-to guy who makes the problems of Los Angeles celebrities, superstar athletes, and business moguls disappear. This powerful family drama unfolds when his Irish gangster father is unexpectedly released from prison, setting off a chain of events that shakes the Donovan family to its core.